2008
DOI: 10.1007/s00330-008-0965-2
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of thrombi using EP-2104R, a fibrin-specific contrast agent: initial results in patients

Abstract: This study was an initial phase II trial in humans of molecular magnetic resonance (MR) imaging for improved visualization of thrombi in vessel territories potentially responsible for stroke using a new fibrin-specific contrast agent (EP-2104R). Eleven patients with thrombus in the left ventricle (n = 2), left or right atrium (n = 4), thoracic aorta (n = 4) or carotid artery (n = 1) as verified by an index examination (ultrasound, computed tomograpy, or conventional MR) were enrolled. All MR imaging was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
130
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(132 citation statements)
references
References 64 publications
(114 reference statements)
1
130
1
Order By: Relevance
“…Transmetallation competition experiments demonstrated that EP-2104R was highly inert toward gadolinium loss, which is an important property for patient safety. Remarkably, EP-2104R is the first MRI molecular imaging agent to advance to human trials (Spuentrup et al 2008).…”
Section: Molecular Imaging Agents Obtained Using Purified Targetsmentioning
confidence: 99%
“…Transmetallation competition experiments demonstrated that EP-2104R was highly inert toward gadolinium loss, which is an important property for patient safety. Remarkably, EP-2104R is the first MRI molecular imaging agent to advance to human trials (Spuentrup et al 2008).…”
Section: Molecular Imaging Agents Obtained Using Purified Targetsmentioning
confidence: 99%
“…More recent advances have led to the development of targeted contrast agents, aimed at cell surface receptors or proteins. Fibrin and elastin represent an essential component of atherosclerotic plaques, play a key role during their development and progression, and have already been established as promising targets 35, 36, 37. With targeted molecular probes, contrast‐enhanced CMR can visualize and quantify proteins and cells of the atherosclerotic vessel wall, which, given clinical translation is successful, may improve assessment of vulnerable plaques and allow for better‐tailored invasive and non‐invasive therapies ( Figure 1 ).…”
Section: Factsmentioning
confidence: 99%
“…The applied dose of 4 -7.5 μmol/kg was significantly lower than the typical non-specific gadolinium-based MR contrast agent dose of 0.1 -0.2 mmol/kg. Finally, this molecular probe was successfully used for detecting thrombi in the aorta, carotid and coronary arteries in a patient; this dem-onstrated that clinical translation of targeted gadoliniumbased molecular MR contrast agents is possible [52]. Larger nanoparticles with more than 50, 000 gadolinium atoms per particle have likewise been successfully employed for in vivo imaging of a jugular thrombus in animals; however, this has not been translated to human application [36].…”
Section: Targeted Molecular Probes For Displaying Plaque Componentsmentioning
confidence: 99%